MODERNIZATION OF ISLAMIC EDUCATION AT DARUL IHSAN ISLAMIC BOARDING SCHOOL, DELI SERDANG - Abi Karami; Zaini Dahlan (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This study aims to uncover the modernization carried out by the Darul Ihsan Islamic Boarding School, Deli Serdang. The aspects studied are modernization in the field of institutions, curriculum, learning methods, infrastructure, and facilities, as well as the learning process. This study uses a qualitative method with a descriptive approach and social history. The descriptive approach is used to describe the modernization of pesantren holistically, while the social history approach is used in the historical aspects of the pesantren comprehensively. The findings of this study are; first, institutionally, this pesantren has the status of a modern pesantren; second, the curriculum used is the religious curriculum under the Ministry of Religion and the general under the Ministry of Education and Culture; third, the method used is student-oriented; fourth, the infrastructure and facilities of the pesantren are very adequate with a modern high-rise building style and even has an elevator.